Diálogos e significados sobre o luto e a morte no contexto escolar: implicações para a atividade docente - Silveira, Viviane Gomes da (2024)
With the resumption of in-person teaching after the COVID-19 pandemic period, the human relationship with grief and death was radically revealed, specifically impacting the school environment and bringing disruptions to teaching activity. Based on this panorama, this research sought to answer the following problem: what are the implications for teaching activity of dialogues about grief and death in the school context? Thus, the present research aimed to understand the meanings of the dialogue about grief and death in the school context for teaching activities. In order to respond to this gap, a structured intervention research was carried out in three meetings in the format of focus groups, with 7 teachers from the third and fourth years of elementary education in the basic education network of a school in the interior of Rio Grande do Sul. Data collection was carried out through the use of the following research instruments: diary fieldwork, sentence completion, focus groups and semi-structured interviews. The focus group meetings and interviews were audio recorded and later transcribed. The data were analyzed using Minayo's dialectical hermeneutics method, in the light of historical-cultural psychology and theories of mourning whose assumptions dialogue with each other. Two categories of analysis were constructed: “mourning in education” and “dictatorship of happiness and mourning in contemporary society”.Carrying out this intervention research, which can also be considered a proposal for continued teacher training, allowed us to understand the teacher's perception on the topic of grief and death in the school context, taking into account subjective and objective aspects and the varied determinants that constitute the context of professional activity, the local reality, the teaching role and the difficulties in dealing with the topic. In the categories of analysis, mourning in education emerged prominently, a morning that is collective and political, and that permeates all other mourning in the school context and directly affecting teaching activity. This intervention research proved to be a powerful tool for welcoming, professional support and transformation of the reality studied.